A Study on Electrical Consumption, All Electric Range, Fuel Economy And Emissions of Plug-in Hybrid Electric Recreation-al Boat (PHERB) Powertrain - Norbakyah, J. S.; Salisa, A. R. (International Journal of Engineering and Technology, 2018)
Plug-in hybrid vehicle (PHEV) have capability to reduce fuel consumption and emission attainment the attention around the world. Marine transportation such as boat also need innovation from conventional to PHEV because marine transportation also contributor to pollution. Plug-in hybrid recreational boat (PHERB) is an innovation for recreational boat in marine transportation industry. This paper is focused on the all-electric range (AER), electrical consumption, fuel economy and emissions at different initial and target state of charge (SOC) of the battery on the PHERB powertrain using different water driving cycle. In this research, the model of PHERB is derived and implemented numerically in the MATLAB/SIMULINK environment with a special energy management strategy (EMS) was built. The analysis of all-electric range (AER) and electrical consumption in different initial and target SOC were studied. Hence, the fuel economy and emission were analyzed and compared.